Sur la frontière du domaine de convergence de Serie de Dirichlet - Miškelevičius, A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Мишкелявнчюс. О границе области сходимости ряда Дирихле A. Miškelevičius. Dirichle eilutės konvergencijos srities pasienis